Talimogene Laherparepvec treatment for mucosal melanoma with metastatic lymph node metastasis: case report - Ingason, Arnar B.; Muruganandam, Venkatesa P.; Chidobem, Ikechukwu; Cintolo-Gonzalez, Jessica; Rehman, Hibba tul (Frontiers in Oncology, 2025)
Mucosal melanoma is a rare and aggressive subtype of melanoma, accounting for approximately 1% of all melanoma cases. Of those, only 4% occur primarily in the vagina. Talimogene Laherparepvec (T-VEC) is a biopharmaceutical medication that is used to treat unresectable malignant melanoma. However, the clinical trials for this treatment option excluded patients with mucosal melanomas. Here we report a case of an 85-year-old female with vaginal melanoma with regional lymph node metastasis that had complete durable response to combined T-VEC and immune checkpoint inhibition treatment. This is, to our best knowledge, the first reported case of T-VEC treatment for vaginal melanoma. It supports findings from case reports demonstrating good response to T-VEC in mucosal melanomas of the urethra, maxillary sinus, and the soft and hard palate. Prospective studies assessing the efficacy of T-VEC in treating mucosal melanoma are needed to confirm these findings.